2019
DOI: 10.1177/1089253219887162
|View full text |Cite
|
Sign up to set email alerts
|

Living Donor Liver Transplantation Following Transcatheter Aortic Valve Implantation for Aortic Valvular Disease

Abstract: Over the last few decades, outcomes with living donor liver transplantation (LDLT) have improved significantly. This has resulted in patients who were denied liver transplantation previously, due to various comorbidities and high risk, now being considered for LDLT. This includes patients with severe valvular heart disease such as aortic stenosis. These patients require aortic valve replacement to help cope with significant perioperative hemodynamic changes. High-risk cardiac procedures like aortic valve repla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…[8][9][10][11] History of cirrhosis or liver disease is frequently an exclusion criterion for randomized controlled trials and only a few observations have shown so far the feasibility of TAVR as a bridge or salvage therapy for patients with end-stage liver diseases (n = 6) or before kidney transplantation (n = 1). [12][13][14][15][16] We report herein 3 additional cases of cirrhotic patients with severe AS who benefited from a TAVR procedure while awaiting LT.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] History of cirrhosis or liver disease is frequently an exclusion criterion for randomized controlled trials and only a few observations have shown so far the feasibility of TAVR as a bridge or salvage therapy for patients with end-stage liver diseases (n = 6) or before kidney transplantation (n = 1). [12][13][14][15][16] We report herein 3 additional cases of cirrhotic patients with severe AS who benefited from a TAVR procedure while awaiting LT.…”
Section: Introductionmentioning
confidence: 99%
“…14 In 2019, Kaliamoorthy et al described 2 cases of patients with infective endocarditis-induced acute aortic regurgitation similar to our case who underwent TAVR and then a subsequent living donor liver transplant successfully. 15 When discussing the potential for TAVR, the concern of the safety of this cardiac procedure in a hemodynamically vulnerable cirrhotic patient population must also be brought to light. A recent 2021 investigation studied the 30-day and 1-year post-TAVR recovery course of over 300 patients with end-stage liver and/or kidney disease in comparison with a population without those comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…110 Additionally, LDLT allows for optimal timing of combined procedures such as coronary artery bypass surgery with LDLT or staged procedures such as LDLT after transcatheter aortic valve insertion. 111,112 Likewise, there is concern surrounding LDLT in patients with cirrhosis secondary to alcoholism due to potential for relapse, but these patients' shortand long-term outcomes have been good. [113][114][115] Given the potential for mortality and significant morbidity for the LDLT donor, the appropriateness of LDLT is controversial for highrisk and high MELD patients such as those with fulminant hepatic failure (FHF) in which the right lobe is almost exclusively necessary.…”
Section: Special Issues In Ldltmentioning
confidence: 99%
“…Patients with moderate aortic or mitral valve stenosis and lower MELD scores can have an LDLT safely then undergo cardiac surgery when their valvular disease progresses 110 . Additionally, LDLT allows for optimal timing of combined procedures such as coronary artery bypass surgery with LDLT or staged procedures such as LDLT after transcatheter aortic valve insertion 111,112 . Likewise, there is concern surrounding LDLT in patients with cirrhosis secondary to alcoholism due to potential for relapse, but these patients' short‐ and long‐term outcomes have been good 113–115 …”
Section: Special Issues In Ldltmentioning
confidence: 99%